Deteminants of Tax Burden in Vietnam - Cung, Nguyen Huu (Advances in Social Sciences Research Journal, 2020)
Taxation is an important tool for each country's government to regulate the economy, distribute income fairly and contribute largely to the state budget. Tax revenue is related to the tax burden. How to achieve tax revenue to ensure an appropriate tax burden rate for the economy and the people is a relatively difficult task for each country. The empirical method is employed on a secondary time series data set during the period 1999-2016 to determine the impact of GDP at current prices, tax revenue, index of economic freedom on tax burden in Vietnam by using a linear approach. The empirical results find that the relationship between gross domestic product and tax burden is a negative sign at 1% significant level. Tax revenue has a positive effect on tax burden at 1% significant level. Economic freedom index has a positive effect on tax burden at 1% significant level. Based on the findings, the article recommends that Vietnam continues to seek positive solutions to enhance the economic growth rate, reducing tax revenue through the transfer of some socio-economic development tasks to the private sector which may be undertaken, strongly equitizing state-owned enterprises, retaining a number of businesses with economy regulatory function and social security.